What Influences Consumers’ Intention to Purchase Innovative Products: Evidence From China - Li, Jie; Guo, Fan; Xu, Jialin; Yu, Zucheng (Frontiers in Psychology, 2022)
Drawing on the theory of planned behavior, we investigate the legitimacy of platform governance and whether consumers with greater ranges of risk propensity are more likely to purchase innovative products. This study develops a moderated mediation model involving risk propensity, cognitive legitimacy, purchase intention and perceived benefit. To examine our hypotheses, we conducted a survey of 315 consumers from Shanghai, China. The results reveal that risk propensity is positively related to consumers’ purchase intentions, in which cognitive legitimacy plays a mediating role. Furthermore, the interaction suggests that perceived benefit moderates the relationship between risk propensity and cognitive legitimacy.